2020
DOI: 10.3389/feart.2020.00291
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Size Distribution (CSD) Analysis of Volcanic Samples: Advances and Challenges

Abstract: Studies of magmatic systems have long used the textures of erupted samples to infer processes that control the location and duration of magma storage and drive volcanic eruptions from these storage regions. Models of volcanic processes and magmatic systems have evolved substantially over the past decades, in large part because of advances in analytical and experimental techniques. Cooling-and decompressionexperiments have greatly enhanced our understanding of crystal textures produced by crystallization associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 138 publications
0
28
0
Order By: Relevance
“…pore size and shape, crystal size and shape, crystal content, presence of microcracks, presence of glass, alteration) (e.g. Toramaru 1990;Blower et al 2003;Wright et al 2009;Shea et al 2010;Voltolini et al 2011;Colombier et al 2017;Cashman 2020). The challenge presented by volcanic rocks is exemplified by a simple comparison between the microstructure of a typical sandstone used in studies of rock deformation (Bentheim sandstone, Germany; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…pore size and shape, crystal size and shape, crystal content, presence of microcracks, presence of glass, alteration) (e.g. Toramaru 1990;Blower et al 2003;Wright et al 2009;Shea et al 2010;Voltolini et al 2011;Colombier et al 2017;Cashman 2020). The challenge presented by volcanic rocks is exemplified by a simple comparison between the microstructure of a typical sandstone used in studies of rock deformation (Bentheim sandstone, Germany; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The crystallization kinetics of groundmass microlites have been studied using experimental approaches (Hammer and Rutherford 2002;Brugger and Hammer 2010;Cashman 2020) and by the analysis of natural samples (Castro and Gardner 2008;Wright et al 2012) to estimate the ascent rate of magmas. In addition, crystallization of nanolites (hereafter, groundmass crystals with ca.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, crystallization of nanolites (hereafter, groundmass crystals with ca. < 1 μm in width; D'Oriano Editorial responsibility: J. Eychenne Mujin and Nakamura 2014;Mujin et al 2017) may control eruption behavior by increasing magma viscosity (Di Genova et al 2017, 2020 and the promotion of late-stage bubble nucleation (Cáceres et al 2020) during magma ascent. Although comparisons of such diverse groundmass microtextures have been made among natural samples from typical eruption styles, detailed descriptions of ash fragments during ongoing eruptions and their comparison between transition phases are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…However, the detailed mechanisms by which ascent, degassing, crystallization and densification processes may be modulated to govern this rich variety in eruptive style are complex, inter-linked, and remain incompletely understood. In intermediate magmas, crystal micro-textures of anhydrous phases such as plagioclase are known to track magma ascent processes and represent an important record of shallow sub-surface dynamics (e.g., Hammer et al, 1999;Cashman and Blundy, 2000;Hammer et al, 2000;Miwa et al, 2009;Wright et al, 2012;Preece et al, 2016;Cashman, 2020;Gaunt et al, 2020;Wallace et al, 2020). Decompression experiments have shown that the final plagioclase micro-textures are a combined result of the decompression rate, decompression path (e.g., single-step or multi-step ascent), final storage pressure, time spent at that pressure, and the composition of the exsolving volatile phase (Hammer and Rutherford, 2002;Couch et al, 2003;Brugger and Hammer, 2010a;Brugger and Hammer, 2010b;Riker et al, 2015;Cichy et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, for facetted crystals the growth rate between different crystal axes becomes more disparate with increasing ΔT (Holness, 2014), leading to more prismatic microlites at high growth rates (Hammer et al, 1999;Bain et al, 2019a). Differences in the phenocryst population resulting from variable rates of decompression and degrees of undercooling may also be expected, such as the extent of anhydrous phenocryst growth (Cashman, 2020) and the extent of breakdown of hydrous phases such as amphibole (Devine et al, 1998).…”
Section: Introductionmentioning
confidence: 99%